(untitled) (International Journal on Stereo & Immersive Media, 2017)
FROM THE OBSERVATORY TO THE CLASSROOM: SPACE IMAGES IN THE KEYSTONE “600 SET” AND “1200 SET” CARMEN PÉREZ GONZÁLEZ IZWT (Interdisciplinary Centre for Science and Technology Studies) Bergische Universität Wuppertal